Carbohydrates, Glycemic Index, and Glycemic Load in Relation to Bladder Cancer Risk - Zhu, Hejia; Mo, Qiwang; Shen, Haixiang; Wang, Song; Liu, Ben; Xu, Xin (Frontiers in Oncology, 2020)
Objective: Epidemiologic studies investigating the association between dietary carbohydrates, as well as glycemic index and glycemic load (markers of carbohydrate quality), and bladder cancer risk have yielded inconsistent results. The aim of the present meta-analysis is to summarize the evidence on this association. Materials and Methods: A comprehensive literature search of articles published by December 2019 was performed in PubMed, Scopus and Web of Science databases. A random-effects model was used to calculate the pooled odds ratios (ORs) and their corresponding 95% confidence intervals (CIs). Results: Twelve observational studies were included in the final analysis. There was no evidence of an association between consumption of carbohydrates and bladder cancer risk (pooled OR, 1.04; 95% CI, 0.92-1.17). Likewise, no statistically significant association between glycemic load and bladder cancer was found (pooled OR, 1.10; 95% CI, 0.85-1.42). However, there was a significant positive association between glycemic index and bladder cancer risk (pooled OR, 1.25; 95% CI, 1.11-1.41). In the dose-response analysis, the pooled OR (95% CI) per 10 units of glycemic index per day was 1.02 (95% CI, 1.01-1.04). Conclusion: In this meta-analysis, glycemic index showed a positive linear association with bladder cancer risk.